Comparative efficacy of artesunate and sulphadoxine-pyrimethamine combination with artesunate and amodiaquine combination in uncomplicated falciparum malaria in children - Jose Meky Mandei; Novie Homenta Rampengan; Suryadi Nicolaas; Napoleon Tatura; Ari Lukas Runtunuwu; Tony Homenta Rampengan (Indonesian Pediatric Society, 2008)
Background Malaria is still an important cause of mortalityand morbidity in children and adults in tropical countries.Multidrug resistance againts chloroquine and sulphadox-ine-pyrimethamine had brought to an introduction ofartemisinin-based combination.Objective To assess the alternative treatment of uncompli-cated falciparum malaria in children using artesunate andsulphadoxine-pyrimethamine combination comparing toartesunate and amodiaquine combination.Methods This is a single-blind randomized trial. Sixty-seven children aged six months to 13 years, were recruited.Thirty-three children were treated with artesunate 4 mg/kgbw/day for three days with an additional sulphadoxine-pyrimethamine (pyrimethamine 1-1.5 mg/kgbw) singledose on the first day, while 34 children were treated withartesunate and amodiaquine base 10 mg/kgbw/day for thefirst two days, then 5 mg/kgbw/day on the third day. Bodytemperature and parasite count were recorded everydayfor at least seven days. The outcomes were fever clearancetime, parasite clearance time, cure rate and side effects. Sta-tistical analysis was performed using the student t-test.Results The statistical analysis showed that there wereno difference between these two groups either in feverclearance time (P>0.05), or in parasite clearance time(P>0.05). The cure rate was 100% in both groups. Vomit-ing was found in one patient treated with artesunate andamodiaquine combination.Conclusion The combination of artesunate and sulpha-doxine-pyrimethamine and combination of artesunateand amodiaquine were found to be equally effective in thetreatment of uncomplicated falciparum malaria in children